2018 Early Career Award - Kassianos, Angelos P. (My University, 2026)
Received the 2018 Early Career Award from the European Health Psychology Society (EHPS) which recognises outstanding research excellence, contributions made to the EHPS and/or contributions to professional practice made by EHPS members within 5 years of their PhD
Keywords: Social sciences